Enhanced Photocatalytic Degradation of Methylene Blue by WO3 Nanoparticles Under NIR Light Irradiation - Yin, Xiuzhao; Liu, Lu; Ai, Fujin (Frontiers in Chemistry, 2021)
Photocatalysts have been paid great attention owing to their excellent performance in the degradation of dangerous organic pollutants. Herein, a novel longitudinally grown WO3 photocatalyst was prepared by using a hydrothermal process, which had strong ultraviolet, visible light absorption, and weak near-infrared (NIR) absorption. The WO3 photocatalyst exhibited excellent performance in the rapid degradation of methylene blue (MB) in industry. The photothermal effect is mainly responsible for the rapid degradation of MB under NIR laser irradiation. Besides, different morphologies and structures affect the degradation of MB. The longitudinally grown enlarged the contact area between photocatalyst and MB, and expanded the scope of the absorption wavelength of light, enhancing the stability of photocatalytic materials. So this unique transverse longitudinal structure exhibited a potential capability for degrading organic pollutants.